A critical evaluation of the content validity of patient-reported outcome measures assessing health-related quality of life in children with cancer: a systematic review - Maria Rothmund; Andreas Meryk; Gerhard Rumpold; Roman Crazzolara; Samantha Sodergren; Anne-Sophie Darlington; David Riedl; the EORTC Quality of Life Group (SpringerOpen, 2023)
Abstract Background With increasing survival rates in pediatric oncology, the need to monitor health-related quality of life (HRQOL) is becoming even more important. However, available patient-reported outcome measures (PROMs) have been criticized. This review aims to systematically evaluate the content validity of PROMs for HRQOL in children with cancer. Methods In December 2021, a systematic literature search was conducted in PubMed. PROMs were included if they were used to assess HRQOL in children with cancer and had a lower age-limit between 8 and 12 years and an upper age-limit below 21 years. The COSMIN methodology for assessing the content validity of PROMs was applied to grade evidence for relevance, comprehensiveness, and comprehensibility based on quality ratings of development studies (i.e., studies related to concept elicitation and cognitive interviews for newly developed questionnaires) and content validity studies (i.e., qualitative studies in new samples to evaluate the content validity of existing questionnaires). Results Twelve PROMs were included. Due to insufficient patient involvement and/or poor reporting, the quality of most development studies was rated 'doubtful' or 'inadequate'. Few content validity studies were available, and these were mostly 'inadequate'. Following the COSMIN methodology, evidence for content validity was 'low' or 'very low' for almost all PROMs. Only the PROMIS Pediatric Profile had 'moderate' evidence. In general, the results indicated that the PROMs covered relevant issues, while results for comprehensiveness and comprehensibility were partly inconsistent or insufficient. Discussion Following the COSMIN methodology, there is scarce evidence for the content validity of available PROMs for HRQOL in children with cancer. Most instruments were developed before the publication of milestone guidelines and therefore were not able to fulfill all requirements. Efforts are needed to catch up with methodological progress made during the last decade. Further research should adhere to recent guidelines to develop new instruments and to strengthen the evidence for existing PROMs.